2017
DOI: 10.1097/phm.0000000000000734
|View full text |Cite
|
Sign up to set email alerts
|

Chest Pain From Hypermobility Responding to Physical Therapy in an Adolescent

Abstract: Hypermobility syndrome usually causes pain in limbs from extension type injuries. The authors report on a 16-yr-old female adolescent with incapacitating chest pain secondary to extreme hypermobility of the chest. This pain led the patient to see multiple specialists without improvement or diagnosis. Physical examination results revealed a very hypermobile patient who was able to internally rotate her shoulders inward until her elbows touched. This unusual hyperextension maneuver was achieved by holding the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Physical health 4. Mental health Pacey, 2013 [ 88 ] Transcutaneous electrical nerve stimulation 5–14 Incontinence symptoms Salem, 2010 [ 97 ] Rehabilitation Strengthening and stability training 16 Chest pain Nash, 2017 [ 79 ] Strengthening and stability training 10 Elbow stability, strength and function Karademir, 2022 [ 68 ] Orthopedic aids Neoprene Wrist/hand splints 14 None Frohlich, 2012 [ 53 ] Foot orthotics 5–15 1. Gait synchrony 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical health 4. Mental health Pacey, 2013 [ 88 ] Transcutaneous electrical nerve stimulation 5–14 Incontinence symptoms Salem, 2010 [ 97 ] Rehabilitation Strengthening and stability training 16 Chest pain Nash, 2017 [ 79 ] Strengthening and stability training 10 Elbow stability, strength and function Karademir, 2022 [ 68 ] Orthopedic aids Neoprene Wrist/hand splints 14 None Frohlich, 2012 [ 53 ] Foot orthotics 5–15 1. Gait synchrony 2.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies offered patients physical interventions, which included either physiotherapy, strengthening, and movement training or a combination, often accompanied by education about GJH. All studies found improvement in pain, injury, and/or strength post-intervention [ 23 , 56 , 79 ]. One study compared knee strengthening exercises either in full ROM or only in a non-hyperextended ROM for children with GJH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased range of motion caused by hypermobility and chronic joint laxity may also cause hyperextension injuries to the supporting ligaments and soft tissue. Particularly in people who are already hypermobile, forces from repeated muscle contractions can strain the ligaments of the chest wall, leading to fatigue and pain (12).…”
Section: Introductionmentioning
confidence: 99%